Dynamics and Stability Analysis of a Power System With a PMSG-Based Wind Farm Performing Ancillary Services - Revel, Gustavo (2014)
This work studies the impact on power system dynamics of wind energy conversion systems based on permanent magnet synchronous generators when they perform ancillary services. The ability of modern variable-speed wind turbines to rapidly modify its active and reactive power is exploited in order to provide additional support to the power grid and enhance the overall stability of the system. A set of control loops are incorporated to the wind farm in order to achieve three supporting tasks: short-term frequency regulation, oscillation damping and voltage regulation. The analysis contemplates the effects of different loading conditions, measurement/communication time delays and control loop gains. Bifurcation diagrams, eigenvalue analysis and nonlinear time-domain simulations are used to assess the power system dynamics. The main contribution of this work is the assessment of wind farm ancillary services on the bifurcation structure of the power system.